EASTERN IMPORTS IN THE AGER TERGESTINUS - Žerjal, Tina (Rei Cretariae Romanae Fautorum Acta, 2024)
In 2002 archaeological rescue excavations at Školarice near Spodnje Škofije (close to Koper) revealed a part of an extensive architectural complex – a roman villa rustica with baths and a wine and olive oil production area. Only the area for the new motorway under construction was excavated. Due to intense farming and the creation of terraces in modern times some of the archaeological layers have been almost entirely destroyed.